La masculinité dans quelques oeuvres des romanciers Francophones Africains,Masculinity in selected works of Francophone African authors - Joseph, Joy Ifeanyichukwu Osarumwense (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2019)
This thesis is a sociocritic and comparative study in Francophone African Literature which examines how male and female authors depict masculinity amongst African men in selected works of Francophone authors and how it affects the emancipation of women in the society. These include Mariama Bâ's Un chant écarlate (1981) from Senegal, Adelaïde Fassinou's Modukpè le rêve brisé (2000) from Benin, Ramonu Sanusi's Le bistouri des larmes (2005, 2010) from Nigeria, Azaratou Baboni's Vie de femme, vie de sang, (2011) from Benin, Ramonu Sanusi's Un nègre a violé une blonde Ã  Dallas, (2016) from Nigeria. The study analyses the various forms of masculinity in the selected works of Francophone authors. The study also examines the notable similarities and differences in the portrayal of male characters in the novel and how prevailing environmental factors determine the themes in the novel. This study has demonstrated that hegemonic and marginalized forms of masculinity are the dominant forms of masculinity in West Africa. These forms of masculinity have negative effects not only on the woman but affects the society in general. Furthermore, the study pleads for a social change with respect to Molara Leslie-Oguundipe's theory on stiwanism (Ogundipe 1994: 229-230) The thesis is made of six chapters. In the first chapter, we outlined the study's subject matter, its aims and objectives, its significance, its assumptions and methodology. In the second chapter, we examined Raewyn Connell's theory of Masculinity and Molara Leslie-Ogundipe's theory of Stiwanism with respect to the selected novels. Raewyn Connell's theory on masculinity a sociological theory was employed in analyzing the social patterns of societal relationships, social interaction and culture, while Molara Leslie-Ogundipe's theory on stiwanism a literary theory mirrored the West African Society. Such analyses helped us in identifying how socio-cultural and religious contexts influence the attitude of men towards women. In the third chapter, we applied sociocritic and comparative analyses between Mariama's Bâ's Un Chant Écarlate and Adelaïde's Fassinou's Modukpè le rêve brisé. The study focuses on how hegemonic and marginalized forms of masculinity influences racial discrimination in mixed marriages, polygamy, unwanted pregnancy, secondary sterility and single motherhood. These masculinities had negative effects on women and the society. The study also analyzed how both male and female characters employed stiwanist strategy in enhancing peace and harmony in the society. In the fourth chapter, the study examined how hegemonic and marginalized forms of masculinity influenced domestic violence, primary sterility, female genital mutilation and its negative and permanent damage to the health of women, the loss of lives of women and children in Ramonu Sanusi's Le bistouri des larmes and Baboni Azaratou's Vie de femme, vie de sang. The study also examined how women can rise above traditional norms with respect to stiwanist activites. The fifth chapter analyzed the influence of socio-cultural and political challenges in a contemporary society with respect to marginalized form of masculinity. In the sixth chapter, the study concluded that hegemonic and marginalized forms of masculinity are the dominant forms of masculinity. These forms of masculinites have negative effects on both sexes (male and female) as well as the society.
Keywords: Masculinity in literature; Men in literature; African fiction (French) -- History and criticism; BaÌ‚, Mariama. Chant eÌ carlate; Fassinou, AdeÌ laiÌˆde, 1955-.Modukpè le rÃªve brisé; Sanusi, Ramonu Abiodun, 1961-.Le bistouri des larmes; Sanusi, Ramonu Abiodun, 1961-.Un nègre a violé une blonde Ã Dallas; Baboni, Azaratou.Vie de femme, vie de sang